Chapter Navegações, descobertas, encontros e reencontros na poesia de Sophia de Mello Breyner Andresen - Loureiro, Maria de La Salette (Studi e saggi, 2021)
Sophia de Mello Breyner Andresen's book Navigations was inspired by the experience of the author's first contact with the East, during a plane trip to Macao to pay homage to Camões. The view of the coasts of Vietnam will have led Sophia to imagine the wonder and astonishment experienced by the Portuguese navigators who first arrived there by sea. Therefore, this book commemorates the Portuguese Discoveries, in the line of Camões and Pessoa, but that takes a new and original look on the theme. Therefore, these Navigations are an initiatory journey, from which results the discovery of Being, that is, in some way, a kind of circumnavigation voyage, the return to the beginning.